Implementasi Kebijakan Pemerintah Daerah Tentang Bantuan Operasional Sekolah Daerah (BOSDA) Bagi Siswa yang Kurang Mampu Studi pada SMA Negeri 16 Bandar Lampung - Refani Ilham; Yulianto Yulianto; Rahayu Sulistyowati (Jurnal Administrativa, 2021)
Abstract BOSDA is a program of lampung provincial government in the form of direct funding to the Secondary Education Unit both public and private in the city of Bandar Lampung where the amount of grants received in schools is calculated based on the number of students unable to each school and the unit cost (Unit Cost) assistance. According to Lampung Governor Regulation Number 29 Year 2017 concerning Technical Guidelines for Operational Assistance of Lampung Provincial Schools in 2017. Schools that received Bosda Assistance in Lampung Province are Bandar Lampung City, West Lampung Regency, North Lampung Regency and Way Kanan Regency. Researchers want to find out the implementation of BOSDA policy in SMA Negeri 16 Bandar Lampung, because in the pre-survey stage there is some disagreement between the residence and the income of parents of BOSDA recipient students. The purpose of this research is to find out the implementation of BOSDA policy and to know the factors that hinder BOSDA in SMA Negeri 16 Bandar Lampung. The research method used is descriptive qualitative with data collection techniques derived from observation, documentation and based on the results of in-depth interviews. The results of this study were described using Charles O. jones toeri namely 1). The organization has an organizational structure issued in accordance with the Decree of the Provincial Education Office ranging from supervisors, persons in charge, chief executives, secretaries, treasurers and survey teams, 2) Inteprertasi the school conducts socialization of the implementation of BOSDA with the announcement and dissemination of information to the community directly, so that the implementation and implementation of BOSDA can be heard by the community directly, 3) Application that the implementation of BOSDA in accordance with technical guidelines and verify prospective BOSDA students with home surveys , facilities owned, parental work, ownership of KIP cards, as well as information from neighbors around the house, BOSDA funds expenditure is also issued according to the RKS submitted to the Provincial Education Office. Bosda implementation is in response by students is very good but needs to be added again quota while the inhibition factor is the disbursement of funds at the end of the semester makes the school have to find loan funds to finance students BOSDA Keywords: Implementation, Factors Operational Assistance For Regional Schools